Gender Dynamics In Public Policy Management In Uganda And South Africa - Basheka, B. C.; Vyas-Doorgapersad, Shikha (African Journal of Public Affairs, 2015)
In recent years, governments in Africa have been under increasing pressure to demonstrate their relevance as citizens demand delivery of better public services. To respond to the numerous calls for efficiency improvements in service delivery governments design and implement a number of public policies that address service delivery problems. The question of how gender dynamics is used to shape public policy management is, though, less understood and has not been subject to enough scholarly attention among policy analysts. The challenges faced by different gender categories differ and ought to be considered in public policy formulation, implementation and review. While a significant amount of scholarly work has been directed at the broad subject of gender in Africa, there remains a dearth of research on gender dynamics specifically relating to public policy management. Also, studies that take a comparative angle on the subject are not a common feature on the continent. In this article, the authors interrogate through a comparative approach the gender dynamics in the public policy management of the water sector policies in South Africa and Uganda. It addresses certain policy and management implications, aiming at bringing to the fore issues of gender as specifically applied to the subject of public policy.